An evolving role in the NICU: a study of the tasks, knowledge, skills, and practice demographics of the neonatal therapist - Fernandez-Fernandez, Alicia; Gibbs, Deanna; Miller, Margaret; Knudsen, Kati; Ferrara-Gonzalez, Louisa; Pineda, Roberta (Frontiers in Pediatrics, 2025)
ObjectivesTo describe current practice and roles of the neonatal therapist.Study designA Neonatal Therapy Practice Analysis was distributed to neonatal therapists (physical therapists, occupational therapists, and speech-language pathologists) in 2019–2020 via social media, email, newsletters, and conference materials.ResultsThere were 1,313 respondents from 1,110 different hospitals. 41.7% (n = 277) were occupational therapists, 29.3% (n = 195) were physical therapists, and 29.0% (n = 193) were speech-language pathologists. 760 (59.1%) worked in level III NICUs, while 248 (19.3%) worked in level II NICUs and 273 (21.2%) in level IV NICUs. 166 (28.1%) of respondents were Certified Neonatal Therapists (CNTs), which was related to higher number of full-time equivalent (FTE) positions per bed (β = 1.066, SE = 0.478, p = 0.026) and higher percentage of infants served in the NICU (β = −3.2, SE = 0.589, p < 0.001). We observed a median of one therapy FTE per 17 NICU beds (range of 1 FTE per 10–200 beds). Higher acuity NICU levels (β = 2.23, SE = 0.197, p < 0.001) and NICUs with higher number of beds (β = 2.497, SE = 0.285, p < 0.001) had more neonatal therapy FTEs. Survey respondents reported working with a median of 76.0% of infants in their respective NICUs (IQR 65%–90%, range 1%–100%). There was a higher percentage of infants served in higher acuity NICUs (β = 4.358, SE = 1.517, p = 0.004), in NICUs with a higher number of beds (β = 0.058, SE = 0.029, p = 0.047), when there was a productivity standard (β=11.47, SE = 1.9, p < 0.001), and where there was a higher number of neonatal therapy FTEs (β = 1.0, SE = 0.239, p < 0.001). 294 (46%) of respondents reported having standing orders, which was related to a higher percentage of infants served in the NICU (β = −1.109, SE = 0.393, p < 0.001) and to having a productivity standard (β = −0.467, SE = 0.139, p < 0.001). 65.3% (n = 415) of respondents reported having productivity standards to meet each day, with a range between 50%–80%.ConclusionThis practice analysis provides insights into the changing landscape of neonatal therapy.